Feasibility Study on Playa del Sur - Esquivias, Eugene Ross S. (College of Engineering, 2005)
The restaurant industry has seen much growth in the Philippines. In 2001, there were already 85,000 listed establishments classified under the restaurant industry and total revenue of P84.84B was generated. The changing times has greatly contributed to this growth. As more people seem to have less time in their hands because of the many demands they have to meet, the restaurant industry finds opportunities for growth by providing the means to save time and energy by preparing and cooking food for the consumer. The primary determinant used in establishing the demand for the restaurant industry is total family expenditures. While the total percentage family expenditures spent on food, declined, from 1991-2000, the percentage spent on food regularly consumed outside of the home increased. From 3.8% in 1991, it has risen to 5.0% in 2000, which is equivalent to P26M. Figures for food consumed at home have fallen while that of food regularly consumed outside the home has risen suggesting the trend of moving the consumption of food from within the home to the food service industry. Another trend that has been observed recently is the increasing health consciousness of people. People today are more health conscious than ever. In a survey conducted by the group, 2 out of every 3 people perceive themselves to be health conscious, 65% actually tried or have thought about going through a special diet, and 71% indicated their willingness to go through a diet if the specialty diet food were readily available in a food establishment such as a restaurant. Recognizing these two trends, the feasibility of Playa del Sur, a specialty diet restaurant was explored. Although there are some restaurants classified as health restaurants, the idea of Playa del Sur is relatively new and this is the advantage that the project will be having over its competitors. The target market identified by the group consisted of the health conscious, people with health problems, women wanting to lose post pregnancy weight, and the general public who dine out. Population statistics on the identified target market were gathered. It was estimated that 0.15% of the said market will be able and willing to try Playa del Sur. On the first year, this amounts to P13M total sales with a complete meal averaging P250. After establishing market feasibility, the technical feasibility was examined. The group started by designing the menu. Menu items were chosen according to the availability of ingredients and the amount of preparation needed. The service level was set at 15 minutes therefore menu items should be quickly prepared and cooked. From the menu, the materials needed were determined and suppliers were evaluated. The same is done for equipment and tools. Food safety is one of the main priorities of the restaurant especially because of its category as a specialty diet ?health? restaurant. For this a system based on HACCP (Hazard Analysis Critical Control Point) is set up to control food safety hazards. The workforce required is composed of a kitchen manager, two cools, a dishwasher, four waiters, and a restaurant manager. At any one time, these are the minimum number of people in the restaurant. A training program is designed for new recruits. Location, on the other hand, is set at Pasay Road in Makati. Based in the technical feasibility and other costs accounted for, the project?s initial cost amounts to P1.04M. In addition to the start up cost, working capital is needed for the first year of operation. A total of P3M is needed as the initial investment to startup the business. To finance the project, all equity financing shall be employed. Financial ratios obtained in the projected financial statements indicate that the project is very profitable. Present worth considering the planning horizon of 5 years is valued at P16.78M. Not only is Playa del Sur financially feasible, it is also very profitable. Aside from being financially profitable, the project is also socially profitable for Filipinos with its benefits great outweighing its costs to society. Benefits include consumer, government employees, and related industries. This is quantitatively shown by its Benefit-Cost Ratio which is equal to 3.01. Based on all the findings from the market, technical, financial and social-profitability phases of the study, it was determined that the overall project Playa del Sur is FEASIBLE, as well as a viable investment for commercial investors.